2003
DOI: 10.1029/2001jd001264
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cosmic ray and El Niño–Southern Oscillation trends in International Satellite Cloud Climatology Project D2 low‐cloud properties

Abstract: The recently reported correlation between clouds and galactic cosmic rays (GCR) implies the existence of a previously unknown process linking solar variability and climate. An analysis of the interannual variability of International Satellite Cloud Climatology Project D2 (ISCCP‐D2) low‐cloud properties over the period July 1983 to August 1994 suggests that low clouds are statistically related to two processes, (1) GCR and (2) El Niño–Southern Oscillation (ENSO), with GCR explaining a greater percentage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 30 publications
(38 reference statements)
7
82
1
1
Order By: Relevance
“…Dickinson (1975) speculated on how ions can influence aerosol nucleation and clouds; later Arnold (1980) suggested that multi ion complexes can serve as condensation nuclei in the stratosphere, and Turco et al (1998) argued that the recombination of ions could nucleate aerosols. In 1997 the role of ionisation from galactic cosmic rays was linked with cloud formation based on satellite observations of clouds and ground based cosmic ray measurements (Svensmark and Friis-Christensen, 1997;Marsh and Svensmark, 2003). A similar connection was later discovered by Harrison and Stephenson (2006) for the UK.…”
Section: Introductionmentioning
confidence: 84%
“…Dickinson (1975) speculated on how ions can influence aerosol nucleation and clouds; later Arnold (1980) suggested that multi ion complexes can serve as condensation nuclei in the stratosphere, and Turco et al (1998) argued that the recombination of ions could nucleate aerosols. In 1997 the role of ionisation from galactic cosmic rays was linked with cloud formation based on satellite observations of clouds and ground based cosmic ray measurements (Svensmark and Friis-Christensen, 1997;Marsh and Svensmark, 2003). A similar connection was later discovered by Harrison and Stephenson (2006) for the UK.…”
Section: Introductionmentioning
confidence: 84%
“…WPWP is one of the special places where the sea surface emits large amounts of water vapor and DMS (Dimethyl Sulfate), due to its high temperature, which are changed to CCN via some processes with GCR. Marsh and Svensmark (2003) indicated the high correlation between GCR and low cloud amount in WPWP for long period data. Another possible explanation Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronization between the flux of galactic cosmic rays and cloud amount has also been reported in terms of the solar cycle (Svensmark, 1998). In a subsequent paper by Marsh and Svensmark (2003), the proposed effect is attributed to low-level clouds. Also in the longer time scale, the synchronization between the cosmic rays and cloud amount is discussed by Miyahara (2008).…”
Section: Introductionmentioning
confidence: 89%
“…Um dos mecanismos propostos para explicar a relação que se observa entre mudanças no clima da Terra e a atividade solaré a modulação da cobertura de nuvens poŕ ıons atmosféricos, produzidos por raios cósmicos [9][10][11][12]. O Sol possui um ciclo de aproximadamente 11 anos, e durante sua fase de máxima atividade, a radiação cósmica (radiação de fundo da galáxia)é bastante atenuada nas camadas superiores de nossa atmosfera por uma espécie de bloqueio magnético.…”
Section: A Importância Do Conhecimento Da Cobertura De Nuvensunclassified